Estratégias de países sul-americanos na formação de recursos humanos para resposta ás emergências de saúde pública: exemplo dos programas de treinamento em epidemiologia de campo - Carvalho, Jonas Lotufo Brant de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Human resources for the detection, investigation and response to public health emergencies are essential and difficult to train. The Field Epidemiology Training Program (FETP) model started in USA in the 1950's and today exists in more than 57 countries. This study aims to describe the FETP training of Argentina, Brazil, Colombia and Peru, as well as their graduates in order to identify common characteristics and to evaluate its contribution in the responses to potential public health emergencies. We conducted two cross-sectional studies: a survey with program coordinators and other with graduates of these programs. The four coordinators answered the survey and all programs address competencies related to: health situation analysis; biostatistics; health communication, prevention and effectiveness, vaccine coverage, management and leadership, informatics applied to health, laboratory use for public health and biosafety, education and mentoring of professionals, disasters preparedness, diseases and communicable and non-communicable events prioritizing, in addition to public health surveillance. Only health professionals can participate in the training, except for the Colombian program. The deliverables to be developed during the training are: investigate and write outbreak or public health emergency report, evaluate a public health surveillance system and perform a planned study. With exception of the Argentinean program, the other programs had years without new selections. The proportion of graduates' responses to the questionnaire was 75% (275) and the most common academic education was medicine, with the exception of the Brazilian program. The improvement in the quality ranged from 95% to 83% and professional recognition, from 84% to 65%. Lower proportion was reported to financial recognition, which ranged from 46% to 29%. Anyway, about 80% reported that the program meets its objectives. Currently, the majority of graduates (55% to ...

Recursos humanos para a detecção, investigação e resposta às emergências são fundamentais e de difícil treinamento. O Field Epidemiology Training Program (FETP) é um modelo de treinamento em serviço, que fora iniciado nos EUA, e existe em mais de 57 países. Esse estudo objetiva descrever os programas de treinamentos FETP da Argentina, Brasil, Colômbia e Peru, bem como, seus respectivos graduados, a fim de identificar pontos em comum e avaliar a sua contribuição nas respostas a possíveis emergências em saúde pública. Realizou-se dois estudos de corte transversal: um inquérito com coordenadores dos programas de FETP e outro com graduados dos referidos programas. Os quatro coordenadores responderam ao questionário e seus respectivos programas abordam: competências nas áreas de análise de situação de saúde, bioestatística, comunicação em saúde, analise econômica, cobertura vacinal, gestão e liderança, informática aplicada a saúde, uso de laboratório para saúde pública e biossegurança, ensino e tutoria dos profissionais, preparação para desastres, priorização de agravos e eventos transmissíveis e não transmissíveis e vigilância em saúde. Somente profissionais formados na área da saúde podem participar do treinamento, com exceção do programa colombiano. As atividades principais a serem desenvolvidos durante o treinamento são: investigar e redigir relatório de surto ou emergências em saúde pública, avaliar sistema de vigilância em saúde e realizar um estudo planejado. Com exceção da Argentina, os programas tiveram interrupção de seleção de turmas. A proporção de respostas dos graduados ao questionário foi de 75% (275) e a formação acadêmica mais frequente foi medicina com exceção do treinamento brasileiro. A melhora na qualificação, variou de 83% a 95% e o reconhecimento profissional, de 84% a 65%. Menor proporção foi relatada para o reconhecimento financeiro que variou de 46%...
Keywords: Recursos humanos na saude publica; Saúde pública - Avaliação; Vigilância sanitária; América do Sul; Public health surveillance